Case Report: Durable response to tumor-infiltrating lymphocyte therapy in a patient with metastatic melanoma and chronic lymphocytic leukemia/small lymphocytic lymphoma - Karapetyan, Lilit; Kuriakose, Joel; Perez, Matthew C.; Ali, Johannes R.; Hall, MacLean S.; Beatty, Matthew S.; Otteni, Christopher D.; Xu, Jin; Kalos, Denise; Moran-Segura, Carlos; Vieira, Ella; Adams, Karla; et al. (Frontiers in Immunology, 2025)
Tumor-infiltrating lymphocyte (TIL) therapy has demonstrated efficacy for the treatment of immune checkpoint therapy-resistant/refractory advanced melanoma patients. However, its safety and efficacy remain to be determined among patients with concurrent chronic lymphocytic leukemia (CLL)/small lymphocytic lymphoma (SLL) and advanced melanoma. This case is the first to demonstrate the successful treatment of a metastatic melanoma patient with concurrent CLL/SLL using lymphodepleting chemotherapy followed by unselected TIL and interleukin-2. The treatment was safe with no new toxicities observed, resulting in a durable radiological partial response and molecular response with the complete clearance of detectable circulating tumor DNA. The microenvironment of the harvested melanoma used to generate the TIL product contained an abundance of CD8+TCF1+ and CD8+CD69+ T cells, spatial co-clustering of CD8+ T cells with CD11c myeloid networks. Despite containing SLL deposits, the harvested melanoma produced a CD8+ T cell-predominant tumor-reactive TIL infusion product containing stem-like CD39negCD69neg CD8+ T cells. A strong overlap (60%) in the TCRβ sequences between this infusion product and peripheral blood mononuclear cells collected at the 9-month follow-up visit was evidence of long-term persistence of TIL in this patient.